Jurisdictional Immunity of International Organizations - Tovar, María del Carmen (1984)
International organizations have an effective presence in the contemporary world, and maintain complicated relations of various types with States, having multiplied in recent decades. The author deals with the jurisdictional immunity of these entities by asking, first, what is the basis of such a prerogative; second, what is its nature in law; and third, what is its scope. The treatment of the subject involves developing the problem of the international personality of the organizations, which is approached through a description and critical evaluation of the main positions. The analysis of the so-called “legal status of the international subject” is also covered. The final part of the work deals with the subject based on Peruvian regulations and the provisions of the Draft Civil Code.